Key Obama officials leave administration. (29th January 2013) - Showstack, Randy
Abstract : Secretary of the Interior Ken Salazar is one of the latest members of the Obama administration to announce that he is leaving his position near the start of President Obama's second term in office. Salazar, who has served as interior secretary since January 2009, intends to leave the department by the end of March, the department noted on 16 January. Salazar joins a number of other key officials who are planning to leave the administration. They include Environmental Protection Agency administrator Lisa Jackson, National Oceanic and Atmospheric Administration administrator Jane Lubchenco, and U.S. Geological Survey director Marcia McNutt.